A Critical Discourse Analysis : Indonesian Government-Mandated Textbook Infusing Islamic and Peace Values - Sofyan Hadi; Dihliza Basya; Endah Nur Tjendani (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Despite the fact that there have been numerous studies into moral values in language textbooks, only a small amount of literature reports the representation of peace or even Islamic values in English for foreign language (EFL) textbooks. As a result, any textbook used by the teacher must contain the essential Islamic and peace values needed to develop students' excellent character. This research is an attempt to carefully examine how Islamic and peace values are portrayed in English Language Teaching (ELT) textbooks for Indonesian junior high school students. Roland Barthes' (1977) semiotic framework and critical discourse analysis Fairclough (2009) (CDA) were chosen as the method for elaborating on Islamic and peace values found in the English textbook as well as the manner in which they are expressed. Findings from Critical Discourse Analysis (CDA) show that the representation of Islamic and peace values such as tolerance, respect, and appreciation for others is distorted. It is hoped that this research will encourage teachers and students to actively participate as intermediaries for the application of values in EFL textbooks. Keywords: Critical Discourse Analysis, ELT textbook, Islamic and Peace Values.